Reactions and Technology of Black Liquor Gasification Combined Synthesis of Dimethyl Ether - Nong, G.Z.; Huang, L.J.; Lu, B.C.; Li, S.Q.; Mo, H.T.; Wang, S.F. (Asian Journal of Chemistry, 2012)
Current research was carried out to develop a technical program for black liquor gasification combined synthesis of dimethyl ether (DME). The chemical reactions and existing technology of black liquor gasification and dimethyl ether synthesis were discussed in detail. Then, bases on the chemical reactions and existing technology, a technical program for black liquor gasification combined synthesis of dimethyl ether was developed, which mainly composed five sections of black liquor gasification, gas desulfurization, CO conversion, synthesis of methanol and synthesis of dimethyl ether. The main technical parameters were chosen as: (1) black liquor gasification: pressure, atmospheric pressure; temperature, 1000 ºC; oxidant, oxygen; mass ratio of oxygen and black liquor, 2-2.5; (2) synthesis of methanol: pressure, 5-7 Mpa; temperature, 227-257 ºC; catalyst: CuO-ZnO-Al2O3 or CuO-ZnO-Cr2O3; (3) synthesis of dimethyl ether: pressure, 1-2 MPa; temperature, 250 ºC-300 ºC; catalyst: g-Al2O3, H-ZSM-5.